Secondary stem lengthening in palms: Response to commentary by Tomlinson and Quinn1. Issue 3 (1st March 2013) - Renninger, Heidi J.; Phillips, Nathan
Abstract : In this response, we address the criticisms put forth by Tomlinson and Quinn ( American Journal of Botany 100: 461–464) about our original publication on secondary stem lengthening in Iriartea deltoidea palms ( American Journal of Botany 99: 607–613) and find areas on which we may agree. We address our figure of a typical palm vascular bundle; the location, timing, and species where secondary lengthening would likely occur; and our measurement of internodes in various palms as well as our choice of individuals. Our original observations were a novel finding in the field of palm biology, and we invite more research and investigation on this subject.